A BIBLIOMETRIC ANALYSIS OF THE TERM “ISLAMIC SOCIAL REPORT”: RESEARCH CLASSIFICATION, RESEARCH TRENDS AND FUTURE DIRECTIONS - Mediawati, Elis; Tullah, Dewi Sarifah; Hasibuan, David HM; Triyono, Bambang (Jurnal Review Pendidikan dan Pengajaran, 2024)
This bibliometric analysis delves into the dynamic landscape of "Islamic Social Report" research, offering insights into the diverse themes and trends within the intersection of Islamic principles and social reporting practices. Through the classification of research clusters, exploration of temporal trends, and examination of citation metrics, the study provides valuable guidance for researchers, policymakers, and practitioners engaged in the realm of Islamic social reporting. However, limitations related to database selection and language bias are acknowledged. Future research opportunities include more inclusive analyses across diverse databases and languages, along with a deeper exploration of specific thematic areas within Islamic social reporting. This study serves as a roadmap for navigating the complexities of the field and informs strategic decision-making for sustainable development within Islamic principles.